Genomic epidemiology of Iranian Bordetella pertussis: 50 years after the implementation of whole cell vaccine - Azadeh Safarchi; Sophie Octavia; Vajihe Sadat Nikbin; Masoumeh Nakhost Lotfi; Seyed Mohsen Zahraei; Chin Yen Tay; Binit Lamichhane; Fereshteh Shahcheraghi; Ruiting Lan (Emerging Microbes and Infections)
Pertussis caused by Bordetella pertussis, remains a public health problem worldwide, despite high vaccine coverage in infants and children in many countries. Iran has been using whole cell vaccine for the last 50 years with more than 95% vaccination rate since 1988 and has experienced pertussis resurgence in recent years. Here, we sequenced 55 B. pertussis isolates mostly collected from three provinces with the highest number of pertussis cases in Iran, including Tehran, Mazandaran, and Eastern-Azarbayjan from the period of 2008-2016. Most isolates carried ptxP3/prn2 alleles (42/55, 76%), the same genotype as isolates circulating in acellular vaccine-administrating countries. The second most frequent genotype was ptxP3/prn9 (8/55, 14%). Only three isolates (5%) were ptxP1. Phylogenetic analysis showed that Iranian ptxP3 isolates can be divided into eight clades (Clades 1-8) with no temporal association. Most of the isolates from Tehran grouped together as one distinctive clade (Clade 8) with six unique single nucleotide polymorphisms (SNPs). In addition, the prn9 isolates were grouped together as Clade 5 with 12 clade-supporting SNPs. No pertactin deficient isolates were found among the 55 Iranian isolates. Our findings suggest that there is an ongoing adaptation and evolution of B. pertussis regardless of the types of vaccine used.